IMMU-16. INTRA-TUMOURAL IL-12 DELIVERY ENABLES CAR T-CELL IMMUNOTHERAPY FOR HIGH-GRADE GLIOMA. (4th December 2020) - Agliardi, Giulia; Liuzzi, Anna Rita; Hotblack, Alastair; De Feo, Donatella; Núñez, Nicolás; Friebel, Ekaterina; Nannini, Francesco; Roberts, Thomas; Ramasawmy, Rajiv; Stowe, Cassandra; Williams, Iwan; Siow, Bernard; et al.
Abstract: Treatment with T-cells redirected to tumour specificity with a chimeric antigen receptor (CAR) may be well suited to treat intracranial tumours due to the ability of T-cells to access the central nervous system and migrate to infiltrative sites of disease. In adult glioblastoma, a case report of local and distant eradication of intracranial and spinal tumour deposits following intraventricular infusion of IL13Ra2-CAR T-cells indicates the potential of this approach. However, in contrast to the sustained complete remissions observed in haematological malignancies, in the majority of patients with glioblastoma CAR T-cell therapy has not resulted in clinical benefit. Tumour heterogeneity and the highly immune inhibitory tumour microenvironment (TME) are likely key barriers to achieving durable anti-tumour immunity. Here use intra-tumoural administration of IL-12 to enable CAR T-cell immunity. We employed CAR-T cells targeting the tumour-specific epidermal growth factor variant III (EGFRvIII). In an immunocompetent orthotopic mouse model of high-grade glioma, we show that CAR-T cells alone failed to control fully established tumour, but when combined with a single, locally delivered dose of IL-12, durable antitumor responses were achieved. IL-12 not only boosted cytotoxicity of CAR T-cells, but also reshaped the TME driving increased infiltration of proinflammatory CD4+ T-cells, decreased numbers of regulatory T-cells (Tregs) and activation of the myeloid compartment. Critically, immunotherapy enabling benefits of IL-12 were achieved with minimal systemic effects. Our findings show that local delivery of IL-12 is an effective adjuvant for CAR-T cell therapy for high-grade glioma. Assessment of application in high-risk childhood brain tumours is ongoing.